Anti-Fragile Leadership: Membangun Sistem SDM yang Justru Semakin Kuat Saat Terjadi Guncangan Pasar - Imellia Faridatus Soleha; Nuril Lailati Syarifah; Juni Indah Sirait; Mochammad Isa Anshori (Jurnal Manajemen Bisnis Digital Terkini, 2026)
Global business environmental uncertainty, triggered by "Black Swan" phenomena, demands that organizations transform beyond passive resilience toward anti-fragility capabilities, where Human Resource (HR) systems actually grow stronger through market disruptions. This study aims to analyze the concept of anti-fragility within organizational leadership, explain the role of transformational leadership in shaping anti-fragile employees, and identify organizational strategies for navigating market uncertainty. The approach employed is a narrative literature review using content analysis techniques across various reputable scientific journals, anti-fragility theory, and organizational case studies such as Disney+, Zoom, and Tractor Supply. Research findings indicate that transformational leadership acts as a primary catalyst that builds anti-fragility through intellectual stimulation, decentralized autonomy, and the creation of a culture that learns from failure. Organizational strategies prioritizing resource flexibility, cross-skilling, and optionality have proven effective in converting crisis stressors into opportunities for innovation and performance growth. The contribution of this article lies in the development of an "Anti-Fragile Leadership" conceptual framework that integrates the philosophical principles of anti-fragility into strategic HRM practices. The practical implications provide a guide for organizational leaders to design work systems that are adaptive and proactive toward market volatility, ensuring that organizations not only survive but thrive from chaos.